Establishment of proliferating callus from roots, cotyledons and Hypocotyls of carob (ceratoniia siliqua L.) seedlings - Martins-Loução, M. A. (2011)
Roots, cotyledons and hypocotyls of Ceratonia siliqua, excised from sterile seedlings produced ed callus on agar with a defined nutrient medium. Callus production takes place in 2-month old ciltures. Percentage callus formation in cotyledons and hypocotyls was greater than in roots. In the cotyledons, callus induction was stimulated in the veins with differentiation of both shoots and roots. Callus growth in the second explant was greatly increased when coconut milk was added to the medium where organogenesis eventually occurred.